Peran Pendidikan Agama dalam Membentuk Karakter dan Akhlak Mulia pada Anak - Amie Primarni; Zahra Algistyani; Maulida Syafitri; Susanti; Mudia Octavia; Ari Lukmanul Hakim (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to analyze the role of religious education in shaping character and noble morals in children and identify the factors that support their success. In the challenging era of globalization, religious education not only functions as an instrument for the introduction of religious values, but also as a mechanism for the formation of civilized and moral behavior. This study uses a qualitative approach with a case study method in several schools that implement intensive religious education. Data was collected through in-depth interviews with religious teachers, parents, and students, direct observation of the learning process in the classroom, and analysis of religious education curriculum documents. Thematic analysis techniques are used to identify the main patterns in religious education and their impact on the formation of children's character. The results of the study show that religious education contributes to strengthening moral values, habituating moral behavior, and synergy between the school environment and family in shaping children's character. However, there are challenges in implementation, such as lack of parental involvement, the influence of digital media, and less innovative learning methods. The limitation of this study lies in the limited scope of the sample in certain schools, so the results cannot be generalized widely. This study makes an original contribution in understanding the crucial factors that affect the effectiveness of religious education in shaping children's character and provides recommendations to improve religious learning methods in the future.